Trade Polices for Electronic Commerce - Mattoo, Aaditya; Schuknecht, Ludger (World Bank, Washington, DC, 2014)
Some countries in the World Trade Organization initially opposed WTO's decision to exempt electronic delivery of products from customs duties, out of concern for the revenue consequences. Others supported the decision as a means of securing open trading conditions. The authors argue that neither the inhibitions nor the enthusiasm is fully justified. First, even if all delivery of digitizable media products moved on-line--an unlikely prospect--the revenue loss for most countries would be small. More important, however, the prohibition of customs duties does not ensure continued open access for electronically delivered products and may even prompt recourse to inferior instruments of protection. Barrier-free electronic commerce would be more effectively secured by deepening and widening the limited cross-border trade commitments under the General Agreement on Trade in Services (GATS), and by clarifying and strengthening certain GATS disciplines.